Reading Strategy’s Failure to Deliver toward Reading Comprehension - A. Gusti Efendy; Gunadi Harry Sulistyo (Graduate School of Universitas Negeri Malang, 2019)
Abstract: The aim of study is investigating the relationship between Support Reading Strategy and reading comprehension. Consequently, the research method to deploy was simple linear regression. Meanwhile, because the population target of the study was all public senior high school students in the municipal area of Malang, East Java, Indonesia, the sample consisted of 301 students from three different schools. Inferring from parametric statistical analysis involving data obtained by conducting Survey of Reading Strategy (SORS) and reading test, the finding indicates that Support Reading Strategy fails to be in good favor toward students’ reading comprehension.Abstrak: Penelitian ini bermaksud mengungkap hubungan antara Support Reading Strategy dan kemampuan memahami bacaan. Untuk itu, peneliti menggunakan metode penelitian regresi linear sederhana. Sementara itu, karena target populasi adalah seluruh siswa SMA negeri di Kota Malang, Jawa Timur, Indonesia, sampel penelitian berjumlah 301 siswa dari tiga sekolah yang berbeda. Berangkat dari analisis statistik parametrik yang mengolah data dari Survey of Reading Strategy (SORS) dan uji kemampuan membaca, temuan penelitian menunjukkan bahwa Support Reading Strategy tidak mampu membuktikan korelasi positif yang signifikan terhadap kemampuan siswa dalam memahami bacaan.